Enjoyment: Subject and World - Thomas, Lis (Emmanuel Levinas, 2004)
In both Time and the Other and Existence and Existents Levinas makes the claim that Heideggerian Dasein is never hungry. In this way he reintroduces the question of the relation between the existent and world. In the last chapter, we saw that he reconfigures the relation of the existent and being by putting the question of the relation of the existent and world to one side. The decision to suspend the existent’s relation to world in the account of il y a is, from a Heideggerian point of view, just as impossible as the account of ontological separation that Levinas offers in these early works. However, for Levinas, just as the existent has a relation to being across a separation, its relation to world also involves an originary movement of separation. For Levinas, this neither moves the question of world to a more theoretical plane, nor reduces it to a physical substratum, but introduces us to the subject of enjoyment who produces an “interval of separation.”